Islamic finances: the way to diversify the economics of Kazakhstan (Journal of Economic Research & Business Administration, 2016)
Most countries see Islamic finance as an alternative system to theexisting traditional one. Because its stability during the financial crisis showed its reliability. As the Islamic finances required to be invested in the real assets, such socially significant industries as agriculture, infrastructure construction can be developed with the help of the Islamic finances. As for Kazakhstan our government takes serious steps to develop this sphere in our country. In this article we offer agriculture for investment attracting from the Islamic world.
Keywords: Islamic finance; Islamic banking; Kazakhstan’s perspectives in attracting investments; agricultural potential of the Kazakhstan; Ijara; Murabaha